Rumah Tahsin Qur’an Roudhotul Jannah’s Role for Kampung Aggaran Karang Tengah Community Reciting Ability Improvement - Nurzanah, Siti; Fudoil, Haikal; Wahyunengsih, Wahyunengsih (Interdisciplinary Social Studies, 2022)
Background: Many factors can affect the learning activities of the Qur'an in children, both from the child himself (an intrinsic factor) and from the child's environment (an extrinsic factor). Some children feel that learning the Qur'an is difficult to understand, while others think that it is easy. Aim: This research aimed to discover the role of RTQ (Rumah Tahsin Qur’an) in teaching the science of the Qur'an in society, especially children and the use of what tahsin method can increase interest in learning and reading Al-Qur'an for residents in Anggran Karang Tengah Village, especially at the age of children at the Roudhotul Jannah Rumah Tahsin Qur'an institution. Method: This research is qualitative. The object of this research is the children who study at the Rumah Tahsin Quran (RTQ). This study involved 2 RTQ supervisors, 2 parents, and 2 children studying at RTQ. The method used was an interview. The instrument used in collecting this data is a question sheet. Findings: The role of this Rumah Tahsin Qur’an in society is as a place for children to learn Quran knowledge such as recitation of the Quran correctly, to guide children in memorizing the Quran, and to make children faster and faster. easy to read the Quran. One of the methods used in achieving the target of memorizing is by way of Murojaah together and always listening to the teacher's Murotal when they want to start learning.